2020
DOI: 10.1097/md.0000000000022304
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of high-frequency cervical spinal cord stimulation in the treatment of refractory trigeminal neuropathy

Abstract: Rationale: Treatment of chronic neuropathic pain in the head and face regions presents a challenge for pain specialists due to the lack of reliable medical and surgical approaches. Patient concerns: A 62-year-old patient came to our attention for an intense facial pain secondary to a lesion of the right trigeminal nerve (all branches) due to a petroclival meningioma. Diagnoses: The patient also presented with gait impairment as well as a defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…There are numerous contributing factors including but not limited to increased awareness of SCS therapy, efforts to minimize or reduce opioid use, emphasis on minimally invasive treatment options, discovery of more diseases amenable to SCS therapy, more physicians trained in utilization of SCS and improved neuromodulation technology. Though SCS was initially used for management of FBSS, its use has expanded to successfully treat other pain syndromes, including but not limited to trigeminal neuropathy,22 chronic abdominal pain,23 post-thoracotomy pain,24 painful diabetic neuropathy25 and non-surgical refractory back pain 26. The success of SCS in treatment of these different pain syndromes has encouraged clinicians and researchers to continue to discover additional pain syndromes that may respond to SCS therapy.…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous contributing factors including but not limited to increased awareness of SCS therapy, efforts to minimize or reduce opioid use, emphasis on minimally invasive treatment options, discovery of more diseases amenable to SCS therapy, more physicians trained in utilization of SCS and improved neuromodulation technology. Though SCS was initially used for management of FBSS, its use has expanded to successfully treat other pain syndromes, including but not limited to trigeminal neuropathy,22 chronic abdominal pain,23 post-thoracotomy pain,24 painful diabetic neuropathy25 and non-surgical refractory back pain 26. The success of SCS in treatment of these different pain syndromes has encouraged clinicians and researchers to continue to discover additional pain syndromes that may respond to SCS therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Only eight other case reports[ 1 , 10 , 15 , 22 , 24 , 25 , 28 ] have described pain relief of at least 50% in a total of 28 patients associated with RTN SCS treatment; furthermore, only two reports detailed permanent implants placed by percutaneous technique with pain relief estimated at about 70%. [ 10 , 26 ] This minimally invasive procedure is not associated with high rates of infections, lead migrations, or skin erosions as reported on gasserian ganglion/peripheral stimulation (26.4%, 17.6%, and 29.4%, respectively),[ 26 ] and does not require an upper cervical or suboccipital incision with the expected surgical site pain as in paddle lead placement and associated morbidity. The reports of these case series collaborate with evidence given.…”
Section: Discussionmentioning
confidence: 99%
“…Research by Peirs et al on mice populations provided limited evidence of such neural networks within the dorsal horn laminae and suggested that the nociceptive fibers were likely to terminate in superficial laminae I and II, while nonnociceptive sensory neurons were likely to innervate the deep laminae III-IV. [23] Only eight other case reports [1,10,15,22,24,25,28] have described pain relief of at least 50% in a total of 28 patients associated with RTN SCS treatment; furthermore, only two reports detailed permanent implants placed by percutaneous technique with pain relief estimated at about 70%. [10,26] is minimally invasive procedure is not associated with high rates of infections, lead migrations, or skin erosions as reported on gasserian ganglion/peripheral stimulation (26.4%, 17.6%, and 29.4%, respectively), [26] and does not require an upper cervical or suboccipital incision with the expected surgical site pain as in paddle lead placement and associated morbidity.…”
Section: Discussionmentioning
confidence: 99%